Clinical manifestations in semilobar holoprosencephaly - Elisa Elisa; A. H. Putranti; E. Mulyono (Paediatrica Indonesiana, 2011)
Holoprosencephaly (HPE) is a brain malformation caused by a primary defect in induction and patterning of the rostral neurotube (basal forebrain) during the first 4 weeks of embryogenesis. T his defect results in incomplete separation of the cerebral hemispheres.Based on the degree of hemispheric nonseparation, HPE traditionally has been classified into three types: alobar, semilobar, and lobar.! In 1963, DeMyer et al. mentioned that defects in brain development may frequently coexist with abnormalities on the midfacial region. T he median facio-cerebral anomalies appear in various associated gradations and combinations.When combined in patterns, these facies always predict a severe, highly characteristic brain anomaly.2